The Role of Community Oversight In Realising Good Governance In The Public Sector - Shindy Aulia; Fitri Panggabean; Mutiara Rezeky; Ema Mauliani; Tiar Marpaung (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the role of public oversight in realizing Good Governance in the public sector. Effective public oversight is expected to strengthen transparency, accountability, participation, efficiency, and justice in government. Although regulations supporting public oversight, such as Law No. 14 of 2008 on Public Information Disclosure and Law No. 25 of 2009 on Public Services, exist, the implementation of public oversight still faces various challenges. This research uses a qualitative approach with a case study analysis to identify the challenges, opportunities, and strategies to enhance the role of public oversight. The findings indicate that public oversight needs to be strengthened through improved access to information, public awareness, and government responsiveness to criticism. This study recommends increasing synergy between the government, society, and non-governmental institutions to create more effective Good Governance.